Agreements on Release of Contractual Liability of Entrepreneurs in Russia and China - S. Zimneva; Xiao He (BRICS Law Journal, 2024)
This article is devoted to a comparative analysis of the provisions of the civil codes of the Russian Federation and the People’s Republic of China regulating the conclusion of agreements on the release or limitation of civil liability. In the context of active trade and economic cooperation between Russia and China, the issues of proper fulfillment of contractual obligations by each of these partners are placed at the forefront of the negotiations. However, the parties may, by means of an agreement between them, provide for cases of exemption from liability in order to minimize their risks from entrepreneurial activity. The authors of this article explore the legal nature and conditions for the conclusion of such agreements, as well as examine the essence of agreements on the release or limitation of liability for an intentional breach of obligation or as a result of gross negligence. A comparative analysis of the provisions of Russian and Chinese civil law leads the authors to conclude that there is a significant similarity in the legal regulation of agreements on exemption from liability for breach of contractual obligations due to the influence of European civil law In addition, the limits of establishing contractual conditions regarding limitations and exemption from liability in accordance with the principle of freedom of contract are examined. Furthermore, the article discusses the recent changes and modifications to the civil laws of Russia and China. These improvements can be used by business partners of the Russian Federation and the People’s Republic of China who are engaged in trade and economic cooperation with these countries when concluding and executing agreements. The results of this study can also be used to study the problems surrounding exemptions from civil liability in contractual obligations in order to further improve the legislation.